Gender Role in Fisheries Value Chain in Asia’s Second Largest Artificial Lake - Jaisamand, Rajasthan - Yadav, Rajpal; Ojha, Shekhar Nath; PS, Ananthan; Yadav, Vinod Kumar; Yadav, Rohitash (Indian Journal of Extension Education, 2020)
Women role is crucial in fisheries and aquaculture worldwide, which has not much acknowledged, valued,Â and excluded from decision-making and leadership positions in their community. The study explores the gender roles in lake fisheries value chain, activity profile, and access to family resources. About 2540 fishers, consisting mainly of tribals, reside in the lake region of Jaisamand and depend on the lake fishing for theirÂ livelihood. Present study sampled 139 sample fisher households to explore the gender roles in lake fisheriesÂ value chain, using a customized tool of gender analytical framework in fisheries. Assessing the activity-profile results ravels that the jointly men and women found to be engaged in four activities, namely fishing, money management, net-mending and family decision. Activities such as boat-repairing, marketing, loading & unloading of fish catch, men found to be engaged except for a tiny percentage of females. Interestingly, inÂ about 20% of households, only women were found to be managing the money and were involved in family decision-making. Men had access to resources, namely land and family equipments, on the other side, both men and women had access to family cash, family labor, training to skill development, education of children.